What modifications should be implemented in the regulation that the Peruvian Income Tax Law grants to thin capitalization? - Dunin-Borkowski Goluchowska, Katarzyna Maria (2019)
The erosion of tax collection via interest reduction is a phenomenon raising major concern to the Peruvian Government. In this context, thin capitalization is a specific clause that limits such actions. However, the outlawed types of thin capitalization are only the ones that erode the base on which the income tax is calculated. In this article, the authors address the Peruvian Income Tax Law considering the Specific Anti-Avoidance Rule for thin capitalization. Moreover, they address the approach recommended by Action 4 of the Base Erosion and Profit Shifting plan as well as the six approaches recommended by the Organization for Economic Cooperation and Development.